Eﬀects of Balance and Proprioceptive Exercises on the Balance of Ice Hockey Players and the Risk of Lower Limb Injuries - Agnė Karvelytė; Saulė Sipavičienė (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Most ice hockey injuries are contact, but about 15% are non-contact musculoskeletal injuries and lower body injuries account for 30-45% of all injuries in ice hockey players. It is believed that proprioception and balance training can improve neuromuscular control, improve its ability to synchronise the muscle joint to improve dynamic stability and improve human performance, so balance and proprioception are suggested exercises as a regular part of training.